TANGGUNG JAWAB HUKUM INTERMEDIARY DALAM MODERASI KONTEN DIGITAL DI INDONESIA: ANALISIS NORMATIF TERHADAP KEPASTIAN HUKUM, AKUNTABILITAS, DAN PERLINDUNGAN HAK DIGITAL - Michael Rayhan Ndraha; Yoga Khirari Haggai; Victor Imanuel Williamson Nalle (Universitas Labuhanbatu, 2026)
The rapid development of Indonesia's digital ecosystem has significantly expanded the role of intermediaries as digital platform providers responsible for managing, filtering, and restricting user-generated content. At the same time, the increasing dissemination of illegal content, hate speech, disinformation, and violations of digital rights has raised fundamental legal questions regarding the scope of intermediary liability in content moderation. Although Indonesia has established a regulatory framework through Law No. 11 of 2008 as amended by Law No. 19 of 2016 on Electronic Information and Transactions, Government Regulation No. 71 of 2019, and Minister of Communication and Informatics Regulation No. 5 of 2020, legal uncertainty remains regarding intermediary liability, accountability mechanisms, and the protection of users' digital rights. This study aims to analyze the legal regulation of intermediary liability in digital content moderation, identify weaknesses in the existing regulatory framework, and formulate legal reform strategies to achieve a balance between freedom of expression and public protection. The research employs a normative juridical method using statutory, conceptual, and comparative legal approaches. The findings demonstrate that Indonesia's regulatory framework remains fragmented and has not comprehensively incorporated the principles of safe harbor, due process, transparent content moderation, and effective platform accountability. These shortcomings contribute to legal uncertainty, inconsistent moderation practices, and potential violations of users' digital rights. This study proposes strengthening Indonesia's legal framework through adaptive regulations, independent oversight mechanisms, proportional implementation of the safe harbor principle, and transparent, participatory governance of digital content moderation to enhance legal certainty and the protection of digital rights.Keywords: intermediary liability, digital content moderation, digital rights, safe harbor, legal accountability.